Multiscale and multimodal imaging for three-dimensional vascular and histomorphological organ structure analysis of the pancreas - Salg, Gabriel Alexander; Steinle, Verena; Labode, Jonas; Wagner, Willi Linus; Studier-Fischer, Alexander; Reiser, Johanna; Farjallah, Elyes; Güttlein, Michelle; Albers, Jonas; Hilgenfeld, Tim; Giese, Nathalia; Stiller, Wolfram; et al. (Scientific reports, 2024)
Exocrine and endocrine pancreas are interconnected anatomically and functionally, with vasculature facilitating bidirectional communication. Our understanding of this network remains limited, largely due to two-dimensional histology and missing combination with three-dimensional imaging. In this study, a multiscale 3D-imaging process was used to analyze a porcine pancreas. Clinical computed tomography, digital volume tomography, micro-computed tomography and Synchrotron-based propagation-based imaging were applied consecutively. Fields of view correlated inversely with attainable resolution from a whole organism level down to capillary structures with a voxel edge length of 2.0 µm. Segmented vascular networks from 3D-imaging data were correlated with tissue sections stained by immunohistochemistry and revealed highly vascularized regions to be intra-islet capillaries of islets of Langerhans. Generated 3D-datasets allowed for three-dimensional qualitative and quantitative organ and vessel structure analysis. Beyond this study, the method shows potential for application across a wide range of patho-morphology analyses and might possibly provide microstructural blueprints for biotissue engineering.
Gesehen am 16.07.2025